The Implementation Of Pertisun As A Policy Innovation In Absorbing Public Aspirations In Merangin Regency - Pahrudin HM; Agus Mustawa; Riant Nugroho; Abdul Halim (Journal of Government and Civil Society, 2022)
ABSTRACTThis study aims to analyze the implementation of Pertisun as a policy innovation in Merangin Regency. The autonomy performance gives the regions sufficient flexibility in managing their territory. Its form is regional development programs based on community inputs. Various studies show that many people’s desires are not accommodated in conventional mechanisms, thus requiring innovative ways. Merangin Regency has Pertisun as a mechanism to pick up people’s aspirations, especially in remote areas. Innovation is an idea, product, information technology, institution, behaviour, values, and new practices or objects that individuals or society perceive as something new. According to van Metter and van Horn, six the performance of public policy implementation, namely: policy size and purpose, resources, characteristics of implementing agents, attitudes and variables affect tendencies of the implementers, inter-organizational communication and implementing activities, and economic, social and political environment. This study was conducted using a qualitative research approach in Merangin Regency. This study found that the implementation of the Pertisun program has been going well as innovative policy in absorbing people’s aspirations. The Pertisun program has been able to increase the role of the community in development activities, especially public aspiration in the development planning stage. Keywords: Policy implementation, policy innovation, local government, Pertisun ABSTRAKPenelitian ini bertujuan untuk menganalisis implementasi Pertisun sebagai inovasi kebijakan di Kabupaten Merangin. Kinerja otonomi memberikan keleluasaan yang cukup bagi daerah dalam mengelola wilayahnya. Wujudnya adalah program pembangunan daerah yang berbasis masukan masyarakat. Berbagai penelitian menunjukkan bahwa keinginan banyak orang tidak terakomodasi dalam mekanisme konvensional, sehingga membutuhkan cara-cara yang inovatif. Kabupaten Merangin memiliki Pertisun sebagai mekanisme penampung aspirasi masyarakat khususnya di daerah terpencil. Inovasi adalah ide, produk, teknologi informasi, institusi, perilaku, nilai, dan praktik atau objek baru yang dirasakan oleh individu atau masyarakat sebagai sesuatu yang baru. Menurut van Metter dan van Horn, enam kinerja implementasi kebijakan publik, yaitu: ukuran dan tujuan kebijakan, sumber daya, karakteristik agen pelaksana, sikap dan variabel yang memengaruhi kecenderungan pelaksana, komunikasi antarorganisasi dan kegiatan pelaksana, serta ekonomi, lingkungan sosial dan politik. Penelitian ini dilakukan dengan menggunakan pendekatan penelitian kualitatif di Kabupaten Merangin. Kajian ini menemukan bahwa implementasi program Pertisun telah berjalan dengan baik sebagai kebijakan inovatif dalam menyerap aspirasi masyarakat. Program Pertisun mampu meningkatkan peran masyarakat dalam kegiatan pembangunan, khususnya aspirasi masyarakat dalam tahap perencanaan pembangunan. Kata Kunci: Implementasi kebijakan, inovasi kebijakan, pemerintah daerah, Pertisun